Influencia de factores climáticos sobre las enfermedades infecciosas. - HUARCAYA CASTILLA, Erick; ROSSI LEYVA, Fiorella; LLANOS-CUENTAS, Alejandro (Revista Médica Herediana, 2013)
Several epidemiological evidence have been correlated with the effect of environmental factors over infectious diseases. Since the El Niño phenomenon in 1973, this event has been incriminated in the onset or trigger of epidemic changes and outbreaks. El Niño, which is responsible for the Ecuatorial Pacific Ocean water warming, produce a global effect, and as a consequence atmospheric humidity and environmental temperature are higher than usual. Currently, there are evidence that those changes have a direct effect on the biological life cycle of infectious diseases vectors and some microorganisms with a correlation in the epidemiology of those diseases. Recently, the molecular biology and the mathematical model analysis have been improving our understood about biological explanations, allowing the opportunity to predict outbreaks, risky areas, or epidemiological changes. We review the current evidence that may affect infectious diseases, as Malaria, Leishmaniasis, Bartonellosis, Cholera and others.